The Role of Business Fields in Increasing West Java Economic Growth Post Covid-19 - Hernita, Nita; Wida Rahmayani, Melia; Riyadi, Wulan; Hakim, Abdul (Universitas Nusantara PGRI Kediri, 2023)
Research aim : This study aims to find out the role of the business field in economic growth in West Java as a result of the post-covid-19 impact. Design/Method/Approach : This study uses a qualitative descriptive method with a review of various literature. Research Finding : The results of this study indicate that the economic growth in West Java that has contracted the most is the Government Administration, Defense and Compulsory Social Security sector, which is minus 6.35% and the fastest improving is the Transportation and Warehousing sector with an economic growth rate in the second quarter of 17.85 %. Efforts to accelerate the improvement of economic recovery in West Java must start from domestic demand which must be maintained by accelerating the economy by strengthening regional fiscal expansion, encouraging investment realization and continuing infrastructure development, as well as the continuity of main business activity activities. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : -